Permintaan Impor (Import Demand) Beras di Indonesia: Pendekatan Analisis Times-Series – Vector Error Correction Model - Helmi Noviar; Rollis Juliansyah (Universitas Teuku Umar, 2019)
This article aims to examine some of the components that affect rice imports in Indonesia in the short and long term through a time-series analysis method approach using the Vector Error Correction model as an approach of estimating commodity specific import demand models. Data series in the period 1975-2015 of variable domestic prices, international rice prices, exchange rates and GDP. Estimation results show only a one-way causality relationship between relative prices, exchange rates and income. While the long-term relationship is not found in this import demand model. Therefore, implications in further research especially in modeling time-series are the main recommendations in this article. Keyword: vector error correction, Import Demand,